Childhood adversities associated with poor adult mental health outcomes in older homeless adults: Results from the HOPE HOME study - Lee, Chuan Mei (Am J Geriatr Psychiatry, 2016)
OBJECTIVE: To examine whether childhood adversity is associated with depressive symptoms, suicide attempts, or psychiatric hospitalization. DESIGN: History of seven childhood adversities (physical neglect, verbal abuse, physical abuse, sexual abuse, parental death, parental incarceration, and child welfare system placement) was gathered through in-person interviews. Multivariate models examined associations between history of childhood adversities and moderate to severe depressive symptoms, lifetime history of suicide attempt, or lifetime history of psychiatric hospitalization. SETTING: General community. PARTICIPANTS: The study enrolled 350 homeless adults, aged 50 and older, in Oakland, CA using population-based sampling methods. MEASUREMENTS: Moderate to severe depressive symptoms measured on a Center for Epidemiologic Studies–Depression Scale (CES-D ≥22), self-reported lifetime history of suicide attempt, and self-reported lifetime history of psychiatric hospitalization. RESULTS: Participants with exposure to one childhood adversity had elevated odds of reporting moderate to severe depressive symptoms (adjusted odds ratio [AOR] 2.0; 95% confidence interval [CI] 1.1–3.7) and lifetime history of suicide attempt (AOR 4.6; 95% CI 1.0–21.6) when compared to those who had none; the odds of these two outcomes increased with exposure to additional childhood adversities. Participants with four or more childhood adversities had higher odds of having a lifetime history of psychiatric hospitalization (AOR 7.1; 95% CI 2.8–18.0); there was no increase with fewer adversities. CONCLUSION: Childhood adversities are associated with poor mental health outcomes among older homeless adults. Clinicians should collect information about childhood adversities among this high-risk population to inform risk assessment and treatment recommendations.